Incidence of Fungal Pneumonia in Children with Acute Myeloid Leukemia Taking Oral Antifungal Prophylaxis: Fungal Pneumonia with Acute Myeloid Leukemia Taking Oral Antifungal Prophylaxis - Iqbal, Luqman; Riaz, Shazia; Gull, Sana; Iqbal, Irsa; Gull, Aimen; Ahmed, Toqeer (Pakistan Journal of Health Sciences, 2025)
Acute leukemia is common in children, with acute lymphoblastic leukemia (ALL) making up 80-85% and acute myeloid leukemia (AML) 10-15%. Objective: To determine the incidence of fungal pneumonia in children with acute myeloid leukemia taking oral antifungal prophylaxis. Methods: In this single-center retrospective study done in a tertiary care hospital, the study analyzed 276 pediatric AML cases from July 2022 to June 2024. The diagnosis of fungal pneumonia was made on the basis of CT scan findings. Demographic and AML subtype data were also analyzed. Results: Among the 276 AML patients enrolled in this study, the mean age of the patients was 8.4 years (range 1-16 years), and there was a male predominance (157 male vs. 119 female). The most common AML subtype was M2 (34.1%), followed by M4 (16.7%) and M5 (8.3%). Out of 276 patients with AML, 69 (25.0%) had CT findings suggestive of fungal pneumonia. M2 and M4 subtypes were the most commonly affected, accounting for about 50% of cases. Conclusions: Children with AML taking oral primary antifungal prophylaxis have a 25% incidence of fungal pneumonia. These findings highlight the importance of vigilant imaging surveillance and targeted interventions in high-risk subgroups (M2 and M4).